Uma comparaç\~ao internacional do estado tecnológico da indústria brasileira (2011) - Luiz Dias Bahia (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper tries to do an international and technological comparison of the Brazilian manufacturing in 2011. The main conclusion is the following: the Brazilian manufacturing has technological supply chains similar to the more developed countries, although it needs development in a few sectors.
Keywords: O57; L69; 330; international comparison; technology; Brazilian manufacturing